2007
DOI: 10.3174/ajnr.a0691
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proton MR Spectroscopy Findings in the Corpus Callosum of Patients with Schizophrenia Suggest Callosal Disconnection

Abstract: BACKGROUND AND PURPOSE:The callosal disconnectivity theory was previously proposed to explain the pathophysiology of schizophrenia. The goal of this study was to investigate the metabolic integrity of the corpus callosum in patients with schizophrenia by proton MR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Indeed, dyscalculic children, known to present deficits in the “number sense” (i.e., difficulties in understanding a quantity and in number sense access), exhibited GM loss in bilateral parietal areas compared to control subjects. Moreover, one study examined the effect of mathematics expertise between two adult groups (Aydin et al, 2007). The data indicated a GM decrease in parietal regions in non-expert.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, dyscalculic children, known to present deficits in the “number sense” (i.e., difficulties in understanding a quantity and in number sense access), exhibited GM loss in bilateral parietal areas compared to control subjects. Moreover, one study examined the effect of mathematics expertise between two adult groups (Aydin et al, 2007). The data indicated a GM decrease in parietal regions in non-expert.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, brain maturation is characterized by loss of gray matter (GM) with age that varies according to brain region (Gogtay et al, 2004). On the other hand, experience-dependent structural plasticity was demonstrated by an increase of GM in cerebral areas associated with training function in expert groups (e.g., mathematicians, Aydin et al, 2007) and was demonstrated during intensive trainings (e.g., motor learning, Draganski et al, 2004; or cognitive training, Draganski et al, 2006). The aim of the present study is to provide insights into the relationships between individual differences in mathematics and brain structure (GM volume variations) in 10-year-old typically achieving schoolchildren.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several important methodological differences between the studies, the main ones being the use of a 3T scanner and quantification with reference to water. Although these findings await further replication in larger studies, it is possible that a biological basis exists for these discrepancies, especially when considering alterations in the T2 of water (Aydin et al, 2007; Flynn et al, 2003; MacKay et al, 2006; Pfefferbaum et al, 1999) and metabolites (Tunc-Skarka et al, 2009) that have been reported in schizophrenia.…”
Section: Imaging Genetics and Neuronal Integrity As Assessed By DI Anmentioning
confidence: 98%
“…Proton magnetic resonance spectroscopy (MRS) has proven itself to be a valuable tool in the study of a number of diseases and disorders including Alzheimer's disease [1][2][3][4][5][6][7], epilepsy [8][9][10][11][12][13][14], Parkinson's disease [15][16][17][18][19][20], multiple sclerosis [21][22][23][24][25], schizophrenia [26][27][28][29][30], bipolar disorder [31][32][33][34][35], stroke [36][37][38], and cancer [39][40][41][42][43]. While a large number of MRS applications have targeted the brain, other anatomical regions have also been studied, including muscle [44,45], breast [46][47][48]…”
Section: Introductionmentioning
confidence: 99%